PERKEMBANGAN SEKOLAH GURU BAWAH (SGB) MUALLIMIN MUHAMMADIYAH DI PULAU PUNJUNG 1964-1970 - Putra, M.Satrio - (Pendidikan Sejarah, 2014)
This article study about Growth Of Sekolah Guru Bawah (SGB) MUALLIMIN MUHAMMADIYAH in PULAU PUNJUNG 1964-1970 research internal issue formulas as follows : Background is forming of SGB Muallimin Muhammadiyah Pulau Punjung, Growth of SGB Muallimin Muhammadiyah Pulau Punjung, switchover of SGB Muallimin Muhammadiyah Pulau Punjung become MTS Muhammadiyah Pulau Punjung. As education study history, this thesis to see growth of Sekolah Guru Bawah (SGB) Muallimin Muhammadiyah in Pulau Punjung. This writing use method research of history which consist of four step that is heuristic ( data collecting and seeking) , criticize source , and interpretation of historiography (writing) ,in 1964 made asw definition early writing because in the year that SGB Muallimin Muhammadiyah founded , to be caused the teacher in Pulau Punjung and west Sumatera generally. in the year 1970 made by final definition bacause SGB Muallimin Muhammadiyah changed with MTS Muhammadiyah Pulau Punjung from result of agrement is official membeof muhammadiyah and see to growth of education of Muhammadiyah in West Sumatera. Inferential that growth of SGB Muallimin have given progress in the field of education in island area of Punjung and i9n area of seiliran Batanghari. SGB yield energy of good teacher during the period, Collage student of SGB Muallimin there is becoming headmaster in MTS Muhammadiyah Pulau Punjung